(untitled) (Encuentros, 2022)
The institutional communication of ecclesiastical organizations is a new thematic frontier for researchers of specialized communication theory due to the great political influence it harbors and the high degree of social diffusion it reaches. This book contains a general analysis of the current Catholic communication channels, but at the same time, it delves into the different and simultaneous discourses of the American Catholic hierarchy. The communicative frameworks that are faced with the challenges of the difficult and historic present are demarcated. What for some is a strategic approach to diversification and survival, for others, including the author of the book, is an essential task to guarantee the vitality of the governing institutions and the internal cohesion of the Catholic community. The legislative and cultural conjunctures are very complex and are perceived as hostile issues; for this reason, the author carries out a series of interpretations that justify the new communicative dynamics in the Catholic world. Throughout the entire publication, very significant concepts such as social evangelization, the transformation of public opinion, ecclesiastical rhetoric, linguistic neutrality, institutional messages, philosophy of information or theological dissemination stand out.